Development of a photoacoustic acquisition system and their proof-of-concept for hemoglobin detection - Bruna Pinheiro; Vânia Pinto; Hugo Dinis; Michael Belsley; Susana Catarino; Graça Minas; Paulo Sousa (Heliyon)
Recently, Organ-on-a-Chip (OoC) platforms have arisen as an increasingly relevant experimental tool for successfully replicating human physiology and disease. However, there is a lack of a standard technology to monitor the OoC parameters, especially in a non-invasive and label-free way. Photoacoustic (PA) systems can be considered an alternative and accurate assessment method for OoC platforms. PA systems combine an illumination source to excite the sample molecules, with an ultrasound sensor to measure the generated ultrasonic waves, combining the advantages of optics and acoustic methodologies to safely acquire tridimensional signals and images at various depths.This work is focused on the design, implementation and test of an acquisition electronics circuit, based on the PA principle, for hemoglobin (Hb) detection, aiming towards a future integration within an OoC platform. Based on the measured frequency response of commercial piezoelectric transducers, an electronics design comprising a differential charge amplifier and a band-pass filter was developed. Experimentally it was verified Hb detection for concentrations of Hb between 2.5 and 10 mg/mL in aqueous solutions, roughly 48 times lower than the typical in vivo blood concentrations. This creates the possibility of developing this technique to monitor Hb at low concentrations in small volumes, which is highly appropriate for OoC devices.